2022
DOI: 10.1002/vetr.1488
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of sheep scab notifications in Scotland, 2014–2019

Abstract: Background Sheep scab is considered an endemic disease of great welfare and economic significance in the UK. Method This paper provides an up‐to‐date assessment of the impact of Sheep Scab (Scotland) Order 2010 on sheep scab notifications in Scotland between 1 January 2014 and 31 December 2019, using data collected by the APHA. Results In total, 564 sheep scab notifications were reported from 503 unique holdings, of which 44 holdings (8.7%) reported more than one incident. The number of notifications did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In this study levels of farmer communication about a disease outbreak to state officials or neighbours was low (Table 9 and 16). This is similar to the findings of O'Brien (1999), who found levels of reporting of sheep scab outbreaks in Ireland to be under 50%, despite it being a legal requirement, alongside suspicions raised by Paton et al (2022) and Jones et al (2022) concerning under-reporting of sheep scab outbreaks. This reluctance may be driven, in part, by shame and the economic consequences of other farmers knowing that a farm has sheep scab, as well as concern over what restrictive actions may result from state involvement.…”
Section: A Co-ordinated Responsesupporting
confidence: 86%
See 2 more Smart Citations
“…In this study levels of farmer communication about a disease outbreak to state officials or neighbours was low (Table 9 and 16). This is similar to the findings of O'Brien (1999), who found levels of reporting of sheep scab outbreaks in Ireland to be under 50%, despite it being a legal requirement, alongside suspicions raised by Paton et al (2022) and Jones et al (2022) concerning under-reporting of sheep scab outbreaks. This reluctance may be driven, in part, by shame and the economic consequences of other farmers knowing that a farm has sheep scab, as well as concern over what restrictive actions may result from state involvement.…”
Section: A Co-ordinated Responsesupporting
confidence: 86%
“…The limited information that is available for the other countries of the British Isles suggests that the disease is currently widespread, but with particular geographic foci (O'Brien, 1992;Bisdorff et al, 2006;Rose et al, 2009;Chivers et al, 2018). The difficulty in obtaining accurate prevalence figures has been recognised (Jones et al, 2022;Paton et al, 2022). Jones et al (2022) demonstrated from state figures for Scotland a prevalence of 0.63% for the period 2014-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation